Strengthening health management, leadership, and governance capacities: What are the actual training needs in Tanzania?. Issue 3 (20th March 2023) - Jiyenze, Mwandu K.; Sirili, Nathanael; Ngocho, James S.; Kikula, Amani; Chikoti, Beatus; Kapologwe, Ntuli; Kengia, James T.
Abstract: Background and Aim: Effective management, leadership, and governance (MLG) contribute to improved population health outcomes. However, weak management, leadership, and governance capacity continue to haunt many health systems in low‐ and‐middle‐income countries (LMICs). Capacity strengthening through training of health system managers is among the strategies to address the latter challenge. However, the actual needs for MLG training remain unestablished in many LMICs. The main objective of this study was to assess the training needs for MLG among health managers in Tanzania Mainland. Methods: We employed a mixed methods approach and convergent mixed methods study design to establish MLG training needs among health managers. In March 2019, quantitative data were collected by administering a questionnaire to a quantitative sample of 156 health managers working in 14 councils and seven regions. We used semi‐structured interviews to collect qualitative data from a qualitative sample of 35 health managers. We used descriptive statistical technique and thematic analysis to analyse quantitative and qualitative data, respectively. Results: The main findings of this study show that: 152 (97%) health managers and all 35 interviewees said that there was a need for training health managers on MLG; 31 out of the 33 proposed MLG competencies were rated as important by the health managers; and a list of 35 general topics and 19 priority topics were suggested by the health managers for inclusion in future MLG training. Conclusion: Our research has generated useful empirical evidence indicating the needs for training health managers on MLG in terms of expressed needs, important competencies, and topics. Policymakers and training developers should use the evidence to develop training programs to address identified needs. Future training needs studies on management and leadership should use observational and diary methods to collect data on the competencies of health managers. Highlights: The actual needs for management, leadership, and governance training remain unestablished in low‐ and‐middle‐income countries (LMICs). This study sought to assess the training needs for management, leadership, and governance among health managers in Tanzania. Majority of study participants expressed the need for training and suggested 31 management, leadership, and governance competencies. Health managers proposed 35 unprioritized and 19 priority topics for management, leadership, and governance training. The findings should inform efforts to strengthen health management, leadership, and governance competencies.